Sophistication about self-control - Deborah A. Cobb-Clark; Sarah Christina Dahmann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We propose a broadly applicable empirical approach to classify individuals as time-consistent versus native or sophisticated regarding their self-control limitations. Operationalizing our approach based on nationally representative data reveals that self-control problems are pervasive and that most people are at least partly aware of their limited self-control. Compared to naifs, sophisticates have higher IQs, better educated parents, and are more likely to take up commitment devices. Accounting for both the level and awareness of self-control limitations has predictive power beyond one-dimensional notions of self-control that neglect awareness. Importantly, sophistication fully compensates for self-control problems when choices involve immediate costs and later benefits. Raising people's awareness of their own self-control limitations may thus assist them in overcoming any adverse consequences.
Keywords: D91; D01; 330; self-control; sophistication; naiveté; commitment devices; present bias